Pengaruh Digital Marketing, Inovasi, dan Word of Mouth terhadap Keputusan Pembelian - Azwar Azwar; Nanda Windi Ani; Aqilla Tauhidta Arla Putri (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study was to analyze the influence of digital marketing, innovation, and word of mouth on purchasing decisions. This research was conducted on klotok coffee consumers in Yogyakarta. The number of samples in this study were 100 (one hundred) respondents who had made a purchase at Kopi klotok Yogyakarta. The technique of taking this sample data is by using a non-probability sampling technique. Data collection was obtained from the results of distributing questionnaires to klotok coffee consumers in Yogyakarta. Data analysis in this study using multiple linear regression analysis. The results of this study indicate that the digital marketing, innovation, and word of mouth variables have a positive and significant effect on the purchasing decision variables. The results of this study indicate that the higher the digital marketing, innovation, and word of mouth it will have a positive impact that will improve purchasing decisions. Keywords: digital marketing, innovation, word of mouth, purchasing decisions